Aksawatra: Inovasi Media Pengenalan Aksara Braile Berbasis Teknologi Touchpad Untuk Meningkatkan Pengetahuan Aksara Jawa Tunanetra di SLBN Semarang - Thahta Ardhika Prabu Nagara; Sava Aurellia Salsabila; Rifki Rochman Ariyanto; Zalfaulislam Sayfanah; Arya Mahardika; Muhammad Sam’an (Jurnal Surya Masyarakat, 2024)
SLBN Semarang, an inclusive school in Semarang City, faces challenges in teaching Javanese script to visually impaired students. The available braille learning media is unable to visualize the original form of Javanese script, resulting in a lack of student motivation. The Aksawatra PKM-PM program offers an innovative solution by introducing Javanese Braille teaching aids based on touchpad technology and 3D models. This innovation allows visually impaired students to experience the script shapes in real time and get audio feedback that helps them understand and remember the script shapes more effectively. The implementation method of this program involves thorough preparation, intensive training for teachers, and implementation of Aksawatra technology learning to blind students. Evaluation results showed significant improvement in students' ability to recognize Javanese script forms and their increased interest in learning. In addition, teachers found it easy to teach Javanese script with this new tool. The Aksawatra PKM-PM program proves that interactive technology can be an effective solution to overcome learning obstacles for visually impaired students, improve literacy skills, and preserve cultural heritage. This success provides a sustainable positive impact for inclusive education and can serve as a model for future learning innovations.